Different techniques of cardiac leads extraction: 17-years single center experience. (2018) - Piro, A; Lavalle, C; Ciccaglioni, A; Alfarano, M; Gatto, M C; Mariani, M V; Straito, M; Schiaffini, G M; Ceccacci, A; Giunta, G; Mancone, M; Fedele, F
No abstract available